Transnational banking supervision and resilience: the SSM case - Marques, Bernardo P. (2021)
In this letter we assess the impact of adopting a transnational supervisor on the resilience of large and complex banks, exploring the establishment of the Single Supervisory Mechanism (SSM) in 2014. Using a differences-in-differences approach, we compare the performance of SSM banks vis-à-vis other banks with a similar size and complexity. Our results suggest that the adoption of a transnational supervisor can improve the resilience of large and complex banks, particularly for those operating in countries with larger banking sectors, higher market concentration and higher supervisory discretion.